The loss of [ei] : [ai] opposition in Middle English - Wełna, Jerzy (Adam Mickiewicz University, 2007)
On the basis of several electronic and online corpora this paper discusses the temporal and regional conditioning of the elimination of the diphthong [ei] in Middle English, a process which led to a restructuring of the system of English diphthongs. The study exploits the so-called impure rhymes found in poetic texts from various areas of England. Although Luick’s hypothesis concerning an early change in the North is not invalidated, the examples adduced here seem to indicate that an early merger of [ei] with [ai] may have also taken place in the northern areas of the West Midland.